A strategic human resource management approach in Chaebol hotels - Mijung Kim; Yeonu Lee (Global Business & Finance Review (GBFR), 2023)
Purpose: The purpose of this study is to examine how strategic human resource management practices are enacted in chaebol hotels, and also to evaluate the relationship between the SHRM practices and organizational effectiveness as experienced by employees, regarding the concept of organizational justice. Design/methodology/approach: The questionnaire survey for employees served to test hypotheses which examine the relationship between SHRM and the influence of these HR practices on organizational effectiveness, using multi-regression analysis. This research encompasses a total of 450 responses collected from individuals employed at chaebol hotels in Seoul and Busan. Findings: This study revealed that chaebol hotels hired competent employees who had language capabilities, used appearance as a selection criterion, and ensured that sophisticated selection methods were well established through the HR systems of numerous subsidiary companies. Employees consider the perceived injustices in the recruitment and selection process and the perceived unfairness in promotions. Research limitations/implications: All findings support the concept that the best practice, driven by collectivism, employment legislation, trade unions, and financial considerations, plays a significant role in managing HRM in chaebol hotels. This study contributes a new SHRM framework by integrating a combination of best fit, based on quality enhancement strategy, and best practices tailored to the specific organization. Originality/value: This study contributed to explore the SHRM framework for the Chaebol hotel sector with regard to providing both high quality of service and also a high price policy. This study provides guidelines for efficient SHRM to managers and practitioners who operate deluxe hotels and offers an essential material to gain a better understanding of a new SHRM framework in service organization.
Keywords: 650; Strategic human resource management; Quality enhancing strategy; Organizational justice; Organizational effectiveness; Chaebol hotels